Money rules for the eurozone candidate countries - Lucjan T. Orlowski (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
This study proposes the adoption of money growth rules as indicator variables of monetary policies by the countries converging to a common currency system, in particular, by the eurozone candidate countries. The analytical framework assumes an inflation target as the ultimate policy goal. The converging countries act in essence as “takers” of the inflation target, which, in this case, is the eurozone's inflation forecast. The study advances a forwardlooking money growth model that might be applied to aid monetary convergence to the eurozone. However, feasibility of adopting money growth rules depends on stable relationships between money and target variables, which are low inflation and stable exchange rate. Long-run interactions between these variables are examined for Poland, Hungary and the Czech Republic by employing a Johansen cointegration test, along with short-run effects assessed with a vector error correction procedure.
Keywords: E42; E52; F36; P24; 330; common currency system; eurozone; monetary convergence; money growth rules; inflation targeting